Assessment of the grid safety values for substation grounding grid design parameters in vertical two-layer soil structure - Permal, Navinesshani; Osman, Miszaina; Mohd Ariffin, Azrul; Ab Kadir, Mohd Zainal Abidin (Universiti Putra Malaysia Press, 2022)
Typically, the impact of the structure of vertically layered soil on the grounding behavior is not considered while designing a substation grounding system. Therefore, it will result in poor grounding designs due to computed inaccurate grid safety values. Besides, no comparative analysis of the grounding design parameters’ impact on the grounding grid systems’ behavior and protection level between vertical and horizontal two-layer soil structures is presently available. Computing and analyzing the grounding behavior of apparent soil resistivity installed in a vertical two-layer soil structure is more challenging than in a horizontal two-layer soil. There are many other parameters to consider, such as the distance ‘a’ between the test electrodes and the angle ‘β’ between the perpendicular line to the soil boundary and the location of the test electrodes. One of the important findings of the assessment shows that the influence of vertically layered soil on grid impedance, step, and touch voltages of a grounding system is insignificant compared to a homogeneous and horizontally layered soil structure. The current flow is affected by an entire grounding grid placed in a specified layer of soil with a specific resistivity for horizontally layered soil. In contrast, soil boundaries separate a grounding grid with various resistivities for vertically layered soil. The outcome of this work is crucial in helping the engineers to understand the behavior of grounding systems in diverse soil conditions and tropical climates.